x3 = x times x times x 3x = x plus x plus x
2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7
That's either the sum or difference of two cubes.
x3 + 2x2 - 3x - 6 = (x2 - 3)(x + 2)
3 - 3x + x2 - x3 = (1 - x)(x2 + 3)
It means that the variable of interest appears as a power in the expression. So, for example, 3x is exponential but x3 is merely cubic. The distinction depends on the position of x.
(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)
x3 + x2 - 3x - 3 x(x2 + x - 3) - 3
4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.
If 3x = 81 then x = 27 and 27 cubed = 19683
(2x + 1)(3x - 1)(3x - 1)
No. Although it is increasing most of the time, it is decreasing between x=-1 and x=1.
3 ln(x) = ln(3x)ln(x3) = ln(3x)x3 = 3xx2 = 3x = sqrt(3)x = 1.732 (rounded)
It is an algebraic expression.
(x - 3)(x2 + 3x + 3)
it means you multiply the number or variable by it self three times.For example,43 = 4*4*4 = 6453 = 5*5*5 = 125x3 = x*x*x3x3 = 3*x*x*x(3x)3 = 3x*3x*3x= 27x3
if that is suppose to be x3 - y12 then you can not factor this further if that is suppose to be 3x-12y then 3(x-4y) is the factored form
(x3 - 3x2 + 4x - 7) - (2x3 + x2 - 3x - 5)
x(x + 1)(x - 3)
x3 + 2x2 + 3x + 6 = x2(x + 2) + 3(x + 2) = (x + 2)(x2 + 3)
Since that isn't an equation, there is really nothing to solve.